External kink related sideways force on the tokamak wall - D. Abate; V. Yanovskiy; L. Cordaro; L. Pigatto; V.D. Pustovitov; D. Terranova; P. Zanca; M. Zuin (Nuclear Fusion)
The external kink related sideways wall force is investigated on ultralow-q RFX-mod plasma discharge. Several theoretical predictions are experimentally verified. The presence of coupled kink modes is observed when the wall is subject to a sideways force. The absence of an integral electromagnetic force on the plasma is analyzed in such conditions. The dependence of sideways force on the mode growth rate is also revealed. A comparison between different theoretical predictions of the sideways force magnitude is performed for both flat-top and ramp-down phases. The results are compared with the direct calculation of sideways force provided by the ex-vessel magnetic measurements. These analyses show that the sideways force related to kink-like mode is much smaller than predicted by models that approximate the plasma as a rigid current-carrying ring or that neglect the presence of the wall.